ISLAMIC GARDEN CONCEPT IN BUSTANUSSALATIN (GARDEN OF THE KINGS), ACEH, INDONESIA - Fakriah, Nurul (Department of Architecture, Faculty of Science and Technology, UIN Maliki Malang, 2021)
In the 17th century, Nuruddin Ar-Raniry wrote a manuscript about the Aceh Kingdom, namely Bustanussalatin, which means the garden of the kings. Following the working title, in one part of the chapter, he described the garden that was a kingdom in detail. This study aims to determine if the garden existed in that era can deliver as an Islamic garden, considering the Kingdom was ruled based on Islamic law. To answer the part of Bustanussalation which described the garden was carried out using the content analysis method. The coding and sorting based on the concept of Islamic garden based on Islamic source, which is the Quran and Hadits, which has been carried out by other research. The result showed that the garden implemented the Islamic garden concept in picturing the garden in Heaven. However, it can not be denied that some restriction in sharia was disobeyed in the garden in using the elements of the causing the garden element historical garden.